Genderová slepota, citlivost, nebo provokace? Polohy a možnosti překladu - Eva Kalivodová (Gender a Výzkum, 2012)
Explaining which circumstances, influences and phenomena enter into the gender of a text, the paper considers the conditions of its translatability. In the first part, examples of English-Czech translations of non-literary and literary texts are chosen for discussion. It is argued that even texts with a feminist potential, i.e. texts in whose themes and forms gender issues are highlighted as an apparent result of the author’s political intention or imaginative work, can lose this potential in the process of being translated into Czech. This is the case in the work of translators who are blind to gender manifestations in the text, and/or who suppress the gender of the translated text in accord with the cultural, textual, and language norms of the target (Czech) culture. In contrast with the quite frequent “gender blindness” of Czech translators, the article in its second part discusses the provocative concepts and approaches of Feminist Translation – a critical discourse and translation practice with its roots in the 1970s Québec. Though a few Czech translations are close to Feminist Translation, the main benefit of introducing it into the Czech milieu is to make the gender of a text an issue, and to work for its acknowledgement through small concrete steps.